Muscles training for the stability of the spine - Maciaszek, Janusz (Akademia Wychowania Fizycznego w Poznaniu)
The aim of the paper is to review various opinions regarding the role of training dedicated to specific muscles in maintaining stability of the spine. Insufficient performance of trunk muscles and resultant changes in motor control lead to decreased stability of spinal segments and unfavorable shift in the distribution of loads in this body region. Disproportion in the strength of trunk muscles in adults is responsible for age-related changes in their body posture. Abdominal muscles are postulated to play particularly important role in postural control and inappropriate tone thereof is considered an etiological factor of back pain. Although a large number of training programs for trunk muscles exists, not all exercises are suitable for individuals of various age, physical fitness and health status. During recent decade, the so-called core stability exercises have been raising a growing interest as a method for spinal stability improvement. The exercises that improve one’s ability to maintain correct body posture at rest and during complex coordinated movements are increasingly recommended by therapists, rather than those aimed solely at the strength gain. A growing body of evidence points to the effectiveness of exercises involving the so-called “abdominal bracing”, i.e. maximal activation of the whole muscular “girdle” of the lower trunk without hollowing the lower abdomen and in a neutral-spine position, causes problem in the control of back pain. Conclusion. Available evidence suggests that it is “abdominal bracing” which constitutes an optimal solution for individuals who suffer from back pain
Keywords: spine; pain; exercise; abdominal muscles